The nigerian micrometeorological experiment (nimex-1): an overview (2004)
The first phase of the Nigerian Micrometeorological Experiment (NIMEX-1) was concluded between 15 February and 10 March 2004, at an agricultural site within the campus of Obafemi Awolowo University in Ile-Ife, Nigeria (7°33’N, 4°33’E). The multi-institutional project was aimed at determining the surface energy balance of a tropical wet and dry location in West Africa. The field observations made fell within a transition from the dry to wet season in the area, and as such, the surface conditions varied in extremes. An integrated measurement system comprising of various micrometeorological sensors was deployed to record the mean and turbulence parameters in the surface layers separately. A number of methodologies viz: the eddy covariance (EC), Bowen ratio energy balance (BREB), and modified Bowen ratio (MBR) systems, used to determine magnitudes of the surface fluxes; sensible and latent heats, were compared. Generally, there is a consistency of their diurnal trends but the BREB method overestimated the surface fluxes up to about 30%. The radiation balance indicated that the incoming shortwave is dominant during daytime and is mainly responsible for the surface forcings. The nonclosure of the energy balance obtained at the surface, typically, was less than 25%.